Associations of TG/HDL Ratio with the Risk of Prediabetes and Diabetes in Chinese Adults: A Chinese Population Cohort Study Based on Open Data - Rongpeng Gong; Yuanyuan Liu; Gang Luo; Wenjing Liu; Ziqi Jin; Zixin Xu; Zheng Li; Lixin Yang; Xiaoxing Wei (International Journal of Endocrinology)
Background. In the global chronic diseases, type 2 diabetes shows a significant upward trend, and there are more people before prediabetes (impaired glucose tolerance). Many patients with impaired glucose tolerance and undiagnosed diabetes do not know that their glucose metabolism system has been in a state of disorder. Every year, about 5% to 10% of prediabetics develop diabetes. One of the important achieving factors may be the increase in blood lipids. However, it is not clear whether the triglyceride/high-density lipoprotein ratio is associated with impaired glucose tolerance and diabetes in the Chinese population. Therefore, we investigated the relationship between triglyceride/high-density lipoprotein and impaired glucose tolerance and diabetes in the Chinese population. Methods. We conducted a retrospective cohort study using data from the health screening program. The study included 116,855 participants from 32 locations in China, all of whom were adults over 20. Participants measured fasting blood glucose levels at each visit and collected information about their diabetes history. Impaired glucose tolerance was diagnosed as fasting blood glucose ≥6.00 mmol and self-reported diabetes mellitus. The patient was measured on the date of diagnosis or on his last visit (whichever comes first). Results. The results showed that, after adjusting the potential confounding factors, the ratio of TG/HDL was positively correlated with the occurrence of prediabetes and diabetes, and there was a saturation effect. The inflection points were 1.04 and 1.33, respectively. The effect value and 95% confidence interval before and after the inflection point of impaired glucose tolerance patients were 1.57 and (1.42, 1.73) and 1.03 and (1.01, 1.05), respectively. The effect value and 95% confidence interval before and after the inflection point in patients with diabetes were 2.07 and (1.80, 2.39) and 1.08 and (1.04, 1.12).